2020
DOI: 10.3892/ol.2020.11728
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of F‑box/WD repeat‑containing protein 7 (Review)

Abstract: The ubiquitin-proteasome system is an important post-translational modification system involved in numerous biological processes, such as cell cycle regulation, gene transcription, signal transduction, apoptosis, differentiation and development. F-box/WD repeat-containing protein 7 (FBXW7) is one of the most studied F-box (FBX) proteins, serving as substrate recognition component of S phase kinase-associated protein 1-Cullin 1-FBX protein complexes. As a tumor suppressor, FBXW7 recognizes numerous proto-oncopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Although not direct evidence, the mutations of diverse arginine residues in human FBXW7 caused an overactivation of multiple kinases involved in cell proliferation, transformation, and metastasis, and arginine and lysine are residues that can undergo diverse post‐translational modifications 29 . FBXW7 is a well‐known E3 ubiquitin ligase regulating various important proteins 30,31 . Furthermore, I‐Tasser showed that the R‐rich C‐terminal region of FBXW24 (Figure 6E) is structurally similar to the R‐rich C‐terminal region of FBXW7 (Figure 6D), which belongs to the WD40 repeat motif (Figure 6C–E and Movie S5).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although not direct evidence, the mutations of diverse arginine residues in human FBXW7 caused an overactivation of multiple kinases involved in cell proliferation, transformation, and metastasis, and arginine and lysine are residues that can undergo diverse post‐translational modifications 29 . FBXW7 is a well‐known E3 ubiquitin ligase regulating various important proteins 30,31 . Furthermore, I‐Tasser showed that the R‐rich C‐terminal region of FBXW24 (Figure 6E) is structurally similar to the R‐rich C‐terminal region of FBXW7 (Figure 6D), which belongs to the WD40 repeat motif (Figure 6C–E and Movie S5).…”
Section: Resultsmentioning
confidence: 98%
“…29 FBXW7 is a well-known E3 ubiquitin ligase regulating various important proteins. 30,31 Furthermore, I-Tasser showed that the R-rich C-terminal region of FBXW24 (Figure 6E) is structurally similar to the R-rich C-terminal region of FBXW7 (Figure 6D), which belongs to the WD40 repeat motif (Figure 6C-E and Movie S5). Generally, a group of several adjacent charged residues might be the key sites for enzymatic activity.…”
Section: Characterization Of Key Sites In Fbxw24 Required For Sycp3 U...mentioning
confidence: 93%
“…Decreased FBXO17 was observed at both the mRNA and protein levels in UCEC tissues and was confirmed to be associated with histological grade. According to previous studies, the dysregulation of F-box proteins in tumors may be ascribed to several causes, such as aberrant DNA methylation [32,33], translational regulation by noncoding RNAs [34], gene mutation or CCAAT/enhancer-binding protein δ (CEBPδ) regulation under hypoxic conditions [35], but the regulation of FBXO17 in UCEC has not been previously shown, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 96%
“…Post-translational modifications of FBXW7 involve its phosphorylation, autoubiquitination, deubiquitination, dimerization, and localization [44].…”
Section: Post-translational Regulation Of Fbxw7mentioning
confidence: 99%